The Capitalist Mode of Production, Their Current Systemic Crisis and a Possible Alternative - Sabogal Tamayo, Julián (Sociedad y Economía, 2015)
In this article, I intend to explain the systemic character of the current world capitalist crisis and illustrate its main components: the workers’ impoverishment, environmental problem and crisis of values. The destructive nature of the capitalist production against the labor class will be shown, as well as its destructive power on nature -one that beco- mes worse especially in moments of crisis. There is an argument about its nature and how such nature is linked to its fundamental contradictions, and also why their fundamental problems don’t have a solution inside the capitalist system. The solution alterna- tives, beyond the capital, suppose the historical nature of this. This is why methodologi- cally the capital should be understood as a social relationship. The method used in these reflections is based on Marx’s thought.